PENGARUH MEDIA TANAH TERHADAP PERTUMBUHAN SEMAI KASUARI PANTAI (Casuarina equisetifolia) - Salija Rumfot; Febian Tetelay; Hendrik S. E. S Aponno (MARSEGU : Jurnal Sains dan Teknologi, 2024)
Coastal Cassowary or Sea Spruce (Casuarina equisetifolia) is one type of biodiversity from coastal ecosystems that need to be preserved. This research was conducted in the nursery of the Forestry Department, Faculty of Agriculture, Pattimura University from March to September 2024. The purpose of this study was to determine the effect of soil media on the growth of Pantai Kasuari seedlings (Casuarina equisetifolia). The method used in this research is Completely Randomized Design (CRD) with 1 treatment and 3 levels, namely Regosol Soil (A0), Mossy Regosol Soil (A1) and Cambisol Soil (A2). The results showed that the A2 treatment (Cambisol Soil) gave the highest results on the height and percentage of plant life followed by the A0 treatment (Regosol Soil).